DETERMINANTS OF PROFITABILITY BASED ON OPERATIONAL EFFICIENCY AND ACCOUNTS RECEIVABLE MANAGEMENT: A STUDY AT PT PEGADAIAN (PERSERO) - Munifa; Nugroho Dwi Prihandoko; Digor Mufti; Muhammad Amin; Nurul Hidayah (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2026)
This research is based on the increase in financing at PT Pegadaian (Persero) which has not been fully accompanied by an increase in operational efficiency and accounting management, so that this condition has the potential to affect the company's profit performance and profitability stability. Based on this, this study aims to analyze the effect of Operating Costs on Operating Income (BOPO) and reporting turnover on the profitability of PT Pegadaian (Persero) for the 2020–2025 period. This study uses a quantitative approach with secondary data from quarterly financial reports and a saturated sample technique of 23 samples, which are then analyzed using multiple linear regression through the classical assumption test, t-test, F-test, and coefficient of determination. The results show that BOPO has a negative and significant effect on profitability, while credit turnover has a positive and significant effect on profitability, simultaneously both variables have a significant effect on ROA with an Adjusted R-Square value of 0.755, which means 75.5% of the variation in profitability is explained by BOPO and circulating turnover. These findings confirm that operational cost efficiency and smooth debt turnover play an important role in increasing Pegadaian's profitability and need to be a focus in the company's financial management strategy.